Reconfigurable Modulation Scheme for Communication System - Mohamed Syed Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In any communication system transmitter and receiver are used to transmit the signal via wired or wireless channel. In the transmitter, modulation is one of the processes to transmit the signal efficiently. Likewise, receiver contains demodulation to recover the original signal from the transmitter. In general, the communication system uses one modulation/demodulation process at a time. It cannot use different modulation/demodulation within a single system. To overcome this problem reconfiguration technique is implemented. It is the method using different modulation scheme at the same time. It will increase the efficiency of the communication system. QPSK and BPSK modulation technique is used to transmit and receive the signal.